Family succession in the rural environment - an analysis based on Thomas Mann's Buddenbrook (Research, Society and Development, 2021)
Currently, family succession in rural areas is still an issue that requires studies to elucidate the problem that surrounds it, even with the reframing and the construction of new social standards. The present work aims to carry out an analysis in the novel "The Buddenbrook - Decay of a Family", correlating with the characteristics found in the present day and the possible processes that can lead to the success or failure of the succession. In the methodological paths, bibliographical and documentary researches with qualitative character were carried out, aiming to deepen the family succession and all the bases and pillars that compose it. The qualitative research conducted here is aimed at validating the object of study presented. Consequently, after analyzing the events contained in the fiction, it was possible to emphasize that family succession should be seen as a process and not as an event, requiring the formation of successors and not only heirs. It is necessary to make training processes for sons and daughters viable, aiming at acquiring knowledge that can be used in the leadership of rural properties and, consequently, in the perpetuation of family businesses. The obstacles presented in the novel can be easily found in rural spaces in Brazil. Based on the work of Thomas Mann, the topics covered could be discussed, and it was found that family relationships form the pillars in the construction of the successor, with the patriarch being primarily responsible for determining the best form of planning.